"After Hello": Exploring Strategies Used by Occupational Therapists Working in Mental Health Settings to Initiate Positive Therapeutic Relationships With Service Users. (2nd October 2022) - Evatt, Mary; Scanlan, Justin Newton
Abstract: The importance of a therapeutic relationship in mental health care is well-established. There is however a need for further research in this field to gain an insight into techniques used by occupational therapists to develop and maintain this all-important relationship. This study uses thematic analysis of semi-structured interviews to explore mental health occupational therapists' understanding of the therapeutic relationship. Three themes were identified: (i) the importance of positive engagement, (ii) specific strategies and techniques used to initiate this relationship and (iii) maintaining boundaries. The study further indicated that the development of therapeutic rapport takes time and opportunities for therapists to engage with service users in seemingly "non-directed" activities should be valued and retained.